2019
DOI: 10.1111/jcpt.13100
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes and practice strategies of community pharmacists towards drug misuse management: A scoping review

Abstract: What is known and objective: Community pharmacists have a key role to play in addressing drug misuse. The objective of this research was to systematically review the current evidence and investigate the attitudes and practice strategies of community pharmacists towards drug misuse management.Methods: Data were extracted from 19 studies retrieved via a three-step search strategy using the Arksey and O'Malley methodological framework for conducting scoping reviews. Results and Discussion: The attitudes and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Empathy lends patients a sense of fulfilment and connectedness that encourages them to reveal their "true state of affairs" and optimises the effectiveness of pharmacist-patient consultations but relatively neglected in healthcare [34]. A systematic review found a clear connection between patients with substance use disorders and negative attitudes, mostly implicit, of healthcare professionals resulting in shorter periods of patient engagement or avoidance of patients [35]. Also, it is reported that once a problematic medication-taking behaviour has been identified, community pharmacists may avoid confronting patients, due to the sensitive nature of PO use, and the potential for patients' perceived sense of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy lends patients a sense of fulfilment and connectedness that encourages them to reveal their "true state of affairs" and optimises the effectiveness of pharmacist-patient consultations but relatively neglected in healthcare [34]. A systematic review found a clear connection between patients with substance use disorders and negative attitudes, mostly implicit, of healthcare professionals resulting in shorter periods of patient engagement or avoidance of patients [35]. Also, it is reported that once a problematic medication-taking behaviour has been identified, community pharmacists may avoid confronting patients, due to the sensitive nature of PO use, and the potential for patients' perceived sense of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have published several pharmacy-related scoping reviews. [12][13][14][15] This commentary will outline the various stages of a JBI scoping review as applied to a review of the characteristics and the outcome measures used to assess the effectiveness of medication safety programs in acute care (See Table 1). 15…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Examples of presentation of results in the pharmacy specific reviews discussed include tabular formats, flow charts and diagrams. 14,27…”
Section: Example Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Community pharmacists are well-positioned for patient-centered roles due to their convenient location and extended hours of operation [1,4]. Hence, it is important to outline ways to support community pharmacists in their roles of changing patients' life styles, reinforcing medication adherence, simplifying dosage regimens, and communicating with patients to establish the desired therapeutic outcomes [3,6]. The simulated patient (SP) approach is widely used to assess practice assessment since it captures a spontaneous observation without individuals being aware of being evaluated [7].…”
Section: Introductionmentioning
confidence: 99%